REKAYASA MEDIA TANAM PADA SISTEM PENANAMAN HIDROPONIK UNTUK MENINGKATKAN PERTUMBUHAN TANAMAN SAYURAN - Aksa, Muhammad; Jamaluddin P, Jamaluddin P; Yanto, Subari (Jurnal Pendidikan Teknologi Pertanian, 2016)
The aim of this research is to improve the growth of vegetable planting through Plant Media Modifying in Hydroponic Planting Systems. This research is an experimental research by using a form of design randomized group (RAK) with 3 treatments and 3 different concentrations, and 3 controls with the same concentration. The experimental method is done with four repetitions. Thus the number of plants being studied is 48 sample. The results showed 3 models of Plant Media Modifying in hydroponic planting system that has been done in this study, overall appears giving contribution to increasing the growth of vegetable planting when compared with group controls. The combination of husked mixture and hull of rice appears the highest contribution, while the lowest contribution toward the growth of vegetable planting is shown through a mixture of husked charcoal and fern roots